2012
DOI: 10.3945/jn.111.149450
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Micronutrient Inadequacy and Risk of High Micronutrient Intakes among Vitamin and Mineral Supplement Users and Nonusers in Canada3

Abstract: Although supplement use is prevalent in North America, there is little information on how supplements affect the prevalence of nutrient adequacy or risk of intakes greater than the tolerable upper intake level (UL). The objectives of this study were to compare the prevalence of nutrient adequacy and percent of intakes greater than the UL from diet alone between supplement users and nonusers and determine the contribution of supplements to nutrient intakes. Dietary intakes (24-h recall) and supplement use (prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 27 publications
11
88
0
Order By: Relevance
“…Data from the CCHS 2.2 showed a 16% prevalence rate of inadequate intakes of vitamin B6 from diet alone in men and 28% in women aged 51y and older (Shakur, et al, 2012). A similar study on 4,384 US residents observed that inadequacy of B6 from diet alone reached 34% among men, and 49% among women aged ≥ 71y (Sebastian, Cleveland, Goldman, & Moshfegh, 2007).…”
Section: Vitamin B6mentioning
confidence: 85%
See 3 more Smart Citations
“…Data from the CCHS 2.2 showed a 16% prevalence rate of inadequate intakes of vitamin B6 from diet alone in men and 28% in women aged 51y and older (Shakur, et al, 2012). A similar study on 4,384 US residents observed that inadequacy of B6 from diet alone reached 34% among men, and 49% among women aged ≥ 71y (Sebastian, Cleveland, Goldman, & Moshfegh, 2007).…”
Section: Vitamin B6mentioning
confidence: 85%
“…Very low prevalence rates of vitamin deficiency (Colapinto, O'Connor, & Tremblay, 2011;MacFarlane, Greene-Finestone, & Shi, 2011) and inadequate intakes (Shakur, Tarasuk, Corey, & O'Connor, 2012) are reported in the Canadian population.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zn requirements (EAR) were met by most children regardless of supplement usage, with the exception of boys aged Supplement use among children has been examined in recent surveys conducted in the USA, Canada, Australia and European countries, with prevalence rates approximating 25-45 % in children and 15-30 % in adolescents. In general, prevalence rates were higher among younger children than pre-adolescents and adolescents (22)(23)(24)(25)(26)(27)(28)(29) . Supplement use among children has been characterised by high parental education and income levels, having better nutrient intakes, lower prevalence of overweight and obesity and having a healthier lifestyle (22,26,28,30) .…”
Section: Discussionmentioning
confidence: 99%